Anatomical and Histological Morphology of The Esophagus and Proventriculus in Green Jungle Fowl (Gallus varius) from Alor Island - Michaela Marisa Dael; Inggrid T. Maha; Filphin A. Amalo; Heny Nitbani (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2021)
Green jungle fowl (Gallus varius) is a species of jungle fowl endemic Indonesia. This study aims to find out the anatomical and histomorphologIcal of esophagus and proventriculus of green jungle fowl from Alor island. Samples of esophagus and proventriculus were taken from 3 green jungle fowl collected in Alor Regency. Macroscopic study observations include size, location, shape, color and consistency, then sample is fixated in a 10% formalin and made histology preparations as well as haemotoxilin-eosin staining. The results showed that the cervical and thoracic esophagus length is 9.8 ± 0.43 cm and 5.5 ± 0.24 cm, and diameters are 0.55 ± 0.11 cm and 0.6 ± 0.22 cm. The green jungle fowl esophagus is pale red, soft constency,and has a smooth outer surface. Histologically, the walls of esophagus are consist of tunica mucosa, tunica submucosa, tunica muscularis ekterna, and tunica adventisia. Proventriculus green jungle fowl length is 3.23 ± 0.21 cm, diameter 1.83 ± 0.24 cm, and weight 2 ± 0 g. The proventriculus is fusiform, pale red in color, and has denser consistency than esophagus. Proventriculus walls are composed of tunica mucosa, tunica submucosa, tunica muscularis ekterna and tunica serosa.